PELAKSANAAN SISTEM RUJUKAN PADA KASUS KEGAWATDARURATAN MATERNAL NEONATAL DI PUSKESMAS KEMBARAN I - Ambarwati, Dewi; Pangesti, Wilis Dwi; Dewi, Sawitri (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2018)
WHO states that one of the main aspects of primary services including maternal and child health is the close relationship with the above levels, this can be seen from how the referral system works effectively. Efforts from the government to reduce MMR and IMR are by holding quality maternal and neonatal health services. Objectives Improve the degree of maternal and child health through effective and efficient health services. Method Qualitative research using a case study research design, through in-depth interviews with implementing midwives, health centers and patients who have received health referrals. Results indicate that the resources and facilities owned by puskesmas are in accordance with APKK and APKR. The funds used by the community are health insurance such as KIS, BPJS, Jamkesmas and Jampersal. The implementation of the referral system has begun with coordination using SIJARIEMAS to the network hospital and consultation with the guardian doctor, management of stabilization of patients with neonatal maternal emergency cases based on SOPs that apply before referral, the process of referring patients to network hospitals using ambulances and accompanied by competent midwives. Conclusion, infrastructure facilities owned by Puskesmas Kembaran I have met the minimum requirements in the implementation of maternal neonatal emergency management and referral implementation process. Keywords: Midwife, Referral System, Emergency Maternal Neonatal, Puskesamas